The effects of the vulnerability of cultural factors on the architectural characteristics of vernacular houses of indigenous tribes in South Cotabato - Dubos, Mary Joy S.; Myrafe S. (2019)
The study was conducted to assess the changes on the architectural characteristics of the houses of the indigenous groups in South Cotabato through identifying the vulnerability of cultural factors and how it influences the changes of these architectural characteristics. The study focused on two tribes in South Cotabato which are the T?boli tribe and B?laan tribe. The changes on the architectural characteristics were categorized into traditional, mixture, and contemporary. A comparative visual analysis was conducted to determine what architectural characteristics are still used, have changed, or have disappeared. The study used key-informant interviews and personal interviews to determine how peoples? lifestyle and beliefs of today caused disappearances or changes on the architectural characteristics of vernacular houses. Based on the results using frequency analysis, there were changes in the architectural characteristics of the present houses of the T?boli and the B?laan tribes. The presences of stilts and open layout have changed. It means that indigenous people rarely used stilts now and have included partitions in the interior layout. The window type of the vernacular house has changed from traditional into a mixture of traditional and contemporary. However, there are also architectural characteristics that have been retained. The indigenous tribes still used the traditional materials for the window which are bamboo and other types of woods. The traditional construction type which is the post-and-lintel construction and the gabled roof style are still being used in the present. These transformations on the architectural characteristics are the reflections of the changes on the cultural factors of the tribes. The changing needs and wants of the people influenced the disappearance of some architectural elements. However, there are also architectural characteristics that have been retained through time.
Thesis (BS Architecture) --University of the Philippines Mindanao, 2019